Processing of Tuna Head By-Products into Antioxidant Peptide Ingredients for Aquaculture Feeds - Raúl Pérez-Gálvez; F. Javier Espejo-Carpio; Pedro J. García-Moreno; Antonio Guadix; Emilia M. Guadix (Antioxidants, 2025)
This study aimed to produce antioxidant peptide fractions from Skipjack tuna (Katsuwonus pelamis) head by-products through enzymatic hydrolysis and membrane filtration. Raw materials were sequentially hydrolyzed with Alcalase® (4 h) and Flavourzyme® (1 h), reaching a final degree of hydrolysis of 18.5 ± 0.9%. The crude hydrolysate was fractionated using ceramic membranes with molecular weight cut-offs of 8, 3, and 1 kDa. Some peptide fractions presented a relevant proportion of short-chain peptides (>50% w/w) and free amino acids (>10% w/w), as well as a high content of essential amino acids (>64% mol), supporting their value as dietary ingredients for aquafeeds. In vitro antioxidant activities were assessed by 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and ferrous ion chelation assays. Some fractions (e.g., F3R1 with IC50 = 1.04 ± 0.01 mg·mL−1 for metal chelating activity) displayed significantly improved (p < 0.05) antioxidant properties compared to the unfractionated hydrolysate (IC50 = 2.75 ± 0.08 mg·mL−1). This may be linked to their molecular weight profile and hydrophobic amino acid content. These results demonstrate the potential of the proposed approach to obtain bioactive peptide fractions with functional properties for aquafeeds. Zootechnical trials are needed to assess their effects on feed utilization and in vivo mitigation of oxidative stress.